2016
DOI: 10.1097/olq.0000000000000460
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Curable Sexually Transmitted Infections in Pregnant Women in Low- and Middle-Income Countries From 2010 to 2015

Abstract: Background Current literature comparing the prevalence rates of curable sexually transmitted infections (STIs) in pregnant women in various global regions is limited. As a result, antenatal screening practices for curable STIs in pregnant women, specifically Treponema pallidum (syphilis), Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), and Trichomonas vaginalis (TV) vary around the world, differing by country and particular STI. Methods We conducted a systematic review of publications on STI prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
84
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 92 publications
10
84
5
Order By: Relevance
“…We found that the associations between chlamydia and spontaneous abortion, infertility and ectopic pregnancy were stronger in low-middle-income countries compared with high-income countries. This finding is consistent with previous work showing a higher prevalence and morbidity of chlamydia in low-middle-income countries compared with high-income countries 11 18. Although research from low-middle-income countries was limited, this difference may suggest disparities in the detection and treatment of chlamydia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the associations between chlamydia and spontaneous abortion, infertility and ectopic pregnancy were stronger in low-middle-income countries compared with high-income countries. This finding is consistent with previous work showing a higher prevalence and morbidity of chlamydia in low-middle-income countries compared with high-income countries 11 18. Although research from low-middle-income countries was limited, this difference may suggest disparities in the detection and treatment of chlamydia.…”
Section: Discussionsupporting
confidence: 92%
“…To better inform modelling studies and policy, more evidence is needed examining the associations between chlamydia infection and adverse pregnancy outcomes. Previous studies estimating the global burden of chlamydia infection18 19 suggested the cost-effectiveness of chlamydia screening among women20 and identified morbidity associated with chlamydia infection in pregnancy as a significant global health problem, especially in low-income and middle-income countries 11 21. In addition, a few studies have confirmed the association between chlamydia infection and pregnancy and fertility-related adverse outcomes 22 23.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high incidence of STIs risk among African adolescent girls [ 49 , 50 ], it is encouraging that both parents and teachers were supportive of school-centered STI screening for adolescent girls. Addressing the issue of disclosure versus non-disclosure of STI screening results to parents is likely to be a cross-cutting issue for research and programs addressing STIs in adolescents throughout Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Latin America show that the prevalence of trichomoniasis is approximately 3.9%, which is higher than the prevalence of Neisseria gonorrhoeae (1.2%) and syphilis (1.1%) [4]. Among pregnant women in Brazil, studies have recorded a prevalence of 7.7% [5].…”
Section: Introductionmentioning
confidence: 99%